A COMPARATIVE STUDY OF PROBLEM SOLVING METHOD AND LANGUAGE GAME IN TEACHING SPEAKING - Andi Tenrisanna Syam (Universitas Syiah Kuala, 2020)
This research aimed to find whether or not there was any significant difference in the speaking achievement of students taught by using language games, compared to those taught by using a problem solving method. This research applied a quasi-experimental design. The sample consisted of 50 students who belong to two groups. The technique of taking sampling was systematic random sampling. The instrument of the research was a structured interview. SPSS 22.0 was used to analyze the data. The researcher found that there was any significant difference in the speaking achievement of the students taught by using language games, compared to those taught by using a problem solving method. In other words, language game was more effective than problem solving method to improve the speaking skill of the fourth semester students of English Study Program at State Islamic Institute of Palopo. The mean score in the language game group was higher than the mean score in the problem solving method group (69.9 43.2). The difference of those mean scores was statistically significant; it is based on t-test value at a significant level 0.05, the probability value was lower than the significant level (0.00 0.05).